2015
DOI: 10.1177/0363546515601970
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Symptomatic Deep Venous Thrombosis and Pulmonary Embolism After Anterior Cruciate Ligament Reconstruction

Abstract: The incidence of VTE after ACL reconstruction in this large population was low. Increased odds of VTE was identified in patients aged ≥35 years with a history of nicotine use, anticoagulant use, concomitant HTO, or concomitant PCL reconstruction. Controlled studies are necessary to determine the efficacy of chemoprophylaxis and to develop evidence-based clinical practice guidelines to minimize VTE after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 17 publications
7
68
2
Order By: Relevance
“…Although advanced age was shown to be the risk factor for DVT after ACLR, other factors, such as preoperative knee pain, revision ACLR and meniscus repair, were not significantly associated with DVT development. Based on a large database analysis, the incidence of DVT after ACLR was reported to be very low, ranging from 0.30% to 0.34% 1–3. In contrast, in a study that used venography to examine for DVT, the incidence was reported to be 14.0%,4 and with US, the incidence was reported to be 9% and 12.1%,5 6 almost the same as the present results.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although advanced age was shown to be the risk factor for DVT after ACLR, other factors, such as preoperative knee pain, revision ACLR and meniscus repair, were not significantly associated with DVT development. Based on a large database analysis, the incidence of DVT after ACLR was reported to be very low, ranging from 0.30% to 0.34% 1–3. In contrast, in a study that used venography to examine for DVT, the incidence was reported to be 14.0%,4 and with US, the incidence was reported to be 9% and 12.1%,5 6 almost the same as the present results.…”
Section: Discussionsupporting
confidence: 75%
“…Since the reported incidence of DVT following ACLR varies from 0.3% to 41.2%1–8 depending on different modalities used in the study and whether asymptomatic or symptomatic DVT was assessed, the true incidence of DVT after ACLR has not been well clarified. The incidence of symptomatic PE was reported to be 0.05%–0.21% from a large database analysis,1–3 but there have only been a few investigations of asymptomatic PE. Therefore, although pharmacological prophylaxis is reported to be effective for reducing DVT after ACLR,9 whether pharmacological prophylaxis is routinely needed after ACLR remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also mentioned VTEs after anterior cruciate ligament reconstruction (ACLR) [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the relevant literature, the reported incidence of VTEs after TKA and ACL reconstruction was 0.36-62.5% [2][3][4], and 0.5% [1,6], respectively. The risk factors associated with VTEs after TKA included advanced age (> 70 years), drain use, and delayed ambulation (≥ 72 h) after surgery [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation